Is Jesus reasonable? a logical analysis of the statements attributed to Jesus Christ - Prichard, Gerald R. (Lanham, Md. : University Press of America, 2009)
"Is Jesus Reasonable? questions the logic of Jesus Christ's words in the Holy Bible. Gerald Prichard, a Bible teacher and Ph.D scientist, details the answers to this question. Specifically, he compares all of the conditional and procedural statements attributed to Christ to each other, as well as to all of the formal rules of human reasoning."--P. [4], cover.
Description based on print version record.
Keywords: Jesus Christ -- Words; Conditionals (Logic); Bible. -- Criticism, interpretation, etc; Jesus Christus -- Logia; Logik; Axiomatik; Vernunft; Electronic books